Menyelami Moralitas dalam Naskah Drama Harut dan Marut dan Malaikat Tersesat dan Termos Ajaib : Sebuah Perbandingan (Semiotika) - Muhammad Fadhlurrahman Zakaria (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study explores the moral values embedded in the plays "Harut dan Marut" by Ali Ahmad Bakatsir and "Malaikat Tersesat dan Termos Ajaib" by R.J. Mardjuki through a semiotic analysis based on Roland Barthes' theory. The research aims to uncover the moral messages conveyed in both scripts, emphasizing the contrasting portrayals of angels and human experiences. The findings indicate that "Harut dan Marut" focuses on the repercussions of disobedience to divine commands, illustrating the gravity of sin and repentance. In contrast, "Malaikat Tersesat" adopts a satirical tone, highlighting the absurdities of human existence and the challenges faced by Adam and Eva. By employing a comparative literature framework, this study enhances the understanding of the moral implications present in these works, demonstrating the role of literature in imparting ethical lessons and fostering moral awareness within society.